2007
DOI: 10.1007/s00228-007-0396-z
|View full text |Cite
|
Sign up to set email alerts
|

The effects of CYP3A4 inhibition on erlotinib pharmacokinetics: computer-based simulation (SimCYP™) predicts in vivo metabolic inhibition

Abstract: Prediction of clinically important drug-drug interaction with SimCYP using in vitro human metabolism data can be a powerful tool during early clinical development to ensure safe administration of anticancer drugs, which are often co-administered at maximum tolerated doses with other drugs as part of a palliative treatment regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(80 citation statements)
references
References 20 publications
3
77
0
Order By: Relevance
“…2), it is advisable to revisit this conclusion. Similarly, studies that have used the ketoconazole model to estimate the true fraction metabolized by CYP3A in vivo should be re-evaluated (Rakhit et al, 2008;Yang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2), it is advisable to revisit this conclusion. Similarly, studies that have used the ketoconazole model to estimate the true fraction metabolized by CYP3A in vivo should be re-evaluated (Rakhit et al, 2008;Yang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary assessments of the ketoconazole-midazolam interaction using that model concluded that predictive performance was poor (Guest et al, 2011). Despite this conclusion, model 2 has been used to determine whether static or dynamic plasma concentration approaches are most appropriate for predicting clinically important DDIs (Einolf, 2007;Guest et al, 2011;Peters et al, 2012), to validate in vitro technologies (Youdim et al, 2008), and to estimate the fraction metabolized by CYP3A (f m ) for new drugs after in vivo studies (Rakhit et al, 2008;Yang et al, 2012). Of importance, model 2 was used by the Food and Drug Administration (FDA) to recommend specific clinical study designs (Zhao et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it cannot be excluded that as a consequence of P-gp and Bcrp1 gene deletion other transporters and/or drug-metabolizing enzymes involved in oral absorption of erlotinib are overexpressed in knockout mice, thus reducing the effect of Bcrp1/P-gp deletion on erlotinib pharmacokinetics. Indeed, considering that recently expression of CYP3A in the intestine has been shown to affect drug absorption (38) and that erlotinib has been reported to be susceptible to CYP3A-mediated metabolism (22,39,40), an altered expression/ activity of CYP3A in our mice model might affect the magnitude of our findings. However, the bioavailability observed in WT mice is of the same magnitude as observed in humans (41) and the experimental condition in this model may thus reflect the pharmacokinetic condition in patients.…”
Section: Effect Of P-gp Bcrp and Mrp2 On Erlotinib Dispositionmentioning
confidence: 95%
“…For COMED, no specific model and parameters were needed according to assumption (2). The CL, F, V d , and k a of the drug of interest would be changed to reflect the effects of COMED (see Simulations and Glossary sections).…”
Section: Pharmacokinetic Modelmentioning
confidence: 99%
“…In the first category, AUC and C max have similar fold changes during DDI. [2,3] The second category includes the cases in which AUC has larger fold changes compared to C max . [4][5][6][7][8] In cases of the third category, C max has larger fold changes compared with AUC.…”
Section: Introductionmentioning
confidence: 99%